The American media publicity and psychological wars - aichouche, Farid; housini, safouane (Journal of Social Sciences and Humanities, 2022)
The great powers noticed a lethal and effective weapon, more powerful than waging wars and running tanks on the battlefields. It is the media propaganda that defeated armies and conquered forces that were classified as heavyweights. The United States of America is a pioneer in using the field of propaganda in various political, military, and economic fields. Opponents have taken its arm and perpetuated the legend of the unbeatable US army. The United States of America, through propaganda, sought to create a local and international public opinion, and then directed it to serve its interests and influence, which is expanding day by day. The media is considered a striking force that the United States manipulates to subject everyone to its hegemony. Through it, America has become the world's arbiter and the court in global traffic and the international policy industry. It hastened to shade the media and inject a terrible torrent of information and news vertically and horizontally in order to destabilize the rest of the countries that see themselves. It, or even those weak countries that try every time to find solutions and get out of their backwardness. The United States of America saw that propaganda would not achieve its goal without waging psychological wars, so it made an empire of its media outlets a frightening trumpet to shake the confidence that some parties have, by conducting psychological wars and managing them from thousands of kilometers away. America's media strategy produced another reality, far different from what the human mind could imagine, so it made the individual a silly game, attracted by false news and shady information. It is owned by any party that it follows, not even its ideologies, within the framework of media globalization that has weakened many, and on the other hand, it served the interests of those who brought